Desenvolvimento de método simples e rápido para determinação multiclasse de resíduos de medicamentos veterinários em rim, fígado e músculo bovino por UHPLC-MS/MS - Rizzetti, Tiele Medianeira (2017)
In food security area, the application of good agricultural practices is a growing concern for public health in the Brazilian domestic market and for the competitiveness countries in the external market. To ensure safety of food from animal origin, monitoring is required and Maximum Residue Limits (MRLs) must be evaluated. Therefore, the development of appropriate analytical methods for residues determination is necessary. In this work a simple, fast and efficient multiclass method of sample preparation was developed for the determination of veterinary drugs residues in bovine kidney, liver and muscle. Determination step was performed by ultra-high-performance liquid chromatographic–tandem mass spectrometry (UHPLC-MS/MS). UHPLC-MS/MS and sample preparation conditions were optimized using experimental designs. Extraction and clean up were performed by solid-liquid extraction and dispersive solid-phase extraction (d-SPE). Central composite designs were used in order to optimize the clean up step. The proposed method was validated using acetonitrile as solvent extraction followed by clean up with EMR-Lipid® sorbent and aqueous solution of 5% trichloroacetic acid (m/v). The proposed method was validated according to the criteria of the European Commission Decision 2002/657/EC. Linearity presented r2 ≥ 0.99 for most the evaluated compounds and recoveries values and RSD in the range recommended by EU. Decision limit (CCα) and detection capability (CCβ) presented values around the maximum residue limits (MRL) of each compound. Monensin was the only compound that did not present satisfactory results for bovine kidney and muscle. The developed sample preparation followed by UHPLC-MS/MS analysis was efficient for the determination of veterinary drug residues in bovine liver, kidney and muscle. The proposed methodology has been successfully applied in real samples and also in proficiency test and proved to be a great option for routine analysis.